Artificial synapse‐based intelligent light‐controlled liquid crystal network actuators - Yuhang Song; Junyao Zhang; Zejun Sun; Haixia Liang; Tongrui Sun; Zhimin Lu; Shucong Li; Yuxing Yao; Xiaoguang Wang; Yang Xu; Jia Huang (InfoMat)
Abstract Various forms of intelligent light‐controlled soft actuators and robots rely on advanced material architectures and bionic systems to enable programmable remote actuation and multifunctionality. Despite advancements, significant challenges remain in developing actuators and robots that can effectively mimic the low‐intensity, wide‐wavelength light signal sensing and processing functions observed in living organisms. Herein, we report a design strategy that integrates light‐responsive artificial synapses (AS) with liquid crystal networks (LCNs) to create bionic light‐controlled LCN soft actuators (AS‐LCNs). Remarkably, AS‐LCNs can be controlled with light intensities as low as 0.68 mW cm−2, a value comparable to the light intensity perceivable by the human eye. These AS‐LCNs can perform programmable intelligent sensing, learning, and memory within a wide wavelength range from 365 nm to 808 nm. Additionally, our system demonstrates time‐related proofs of concept for a tachycardia alarm and a porcupine defense behavior simulation. Overall, this work addresses the limitations of traditional light‐controlled soft actuators and robots in signal reception and processing, paving the way for the development of intelligent soft actuators and robots that emulate the cognitive abilities of living organisms.